2017
DOI: 10.1186/s40662-017-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Small incision lenticule extraction (SMILE) in the correction of myopic astigmatism: outcomes and limitations - an update

Abstract: Small Incision Lenticule Extraction (SMILE) is a flap-free intrastromal technique for the correction of myopia and myopic astigmatism. To date, this technique lacks automated centration and cyclotorsion control, so several concerns have been raised regarding its capability to correct moderate or high levels of astigmatism. The objective of this paper is to review the reported SMILE outcomes for the correction of myopic astigmatism associated with a cylinder over 0.75 D, and its comparison with the outcomes rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…[7][8][9] However, there is still some controversy when it comes to treating astigmatism with SMILE. 10 Some patients who have SMILE may have a resultant refractive error, induced astigmatism, or regression. 10,11 If their resultant refractive error is significant enough, these patients may seek further refractive correction or enhancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] However, there is still some controversy when it comes to treating astigmatism with SMILE. 10 Some patients who have SMILE may have a resultant refractive error, induced astigmatism, or regression. 10,11 If their resultant refractive error is significant enough, these patients may seek further refractive correction or enhancement.…”
mentioning
confidence: 99%
“…10 Some patients who have SMILE may have a resultant refractive error, induced astigmatism, or regression. 10,11 If their resultant refractive error is significant enough, these patients may seek further refractive correction or enhancement. Re-treatment rates after SMILE have not been extensively reported, but Re-instein et al 12 reported a 4% enhancement rate after low myopic treatment (spherical equivalent [SE] up to -3.50 diopters [D] and cylinder up to 1.50 D).…”
mentioning
confidence: 99%
“…13,20−23 Several adjustments of current treatment nomograms have been suggested, leading to a 10% increment in the magnitude of astigmatism correction. 4,24 Currently, however, there are no standardized nomograms for astigmatism correction.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, despite advancements in femtosecond and excimer lasers, refractive corrective surgeries have a definite impact on the biomechanical properties of cornea. [1][2][3][4][5][6] However, despite advancements in femtosecond and excimer lasers, refractive corrective surgeries have a definite impact on the biomechanical properties of cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal refractive surgery is performed worldwide for correction of myopia, myopic astigmatism and hyperopia. [1][2][3][4][5][6] However, despite advancements in femtosecond and excimer lasers, refractive corrective surgeries have a definite impact on the biomechanical properties of cornea. [7][8][9][10] The creation of a flap in laser in situ keratomileusis (LASIK) plus ablation with excimer laser, removal of a lenticule from corneal stroma in small incision lenticule extraction (SMILE), and ablation of Bowman's layer in photorefractive keratectomy (PRK), all lead to weakening of anterior stroma and decrease in corneal stiffness.…”
Section: Introductionmentioning
confidence: 99%